1980
DOI: 10.1136/vr.106.25.532
|View full text |Cite
|
Sign up to set email alerts
|

Renal cysts in pigs: prevalence and pathology in slaughtered pigs from a single herd

Abstract: An abattoir investigation into kidney condemnations due to renal cysts in pork pigs from one producer showed a prevalence of 47.5 per cent. Affected pigs were the progeny of a landrace boar. Similar cysts found in a small sample of day-old piglets sired by the same boar indicated a congenital origin. A marked variation in size and frequency of cysts in the kidneys of slaughtered pigs was seen, some resembling the severity of polycystic kidneys. Histologically cysts appeared to be of tubular origin. The prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…a and b). These cysts are a frequent occurrence in Danish Landrace pigs and are characterized as water‐filled tissue components . As seen in Figure , this fact is supported by an absence of urea infiltration into the cyst.…”
Section: Resultsmentioning
confidence: 65%
“…a and b). These cysts are a frequent occurrence in Danish Landrace pigs and are characterized as water‐filled tissue components . As seen in Figure , this fact is supported by an absence of urea infiltration into the cyst.…”
Section: Resultsmentioning
confidence: 65%
“…Polycystic renal diseases in other species is in most cases associated with normal-sized to enlarged kidneys. 6,[18][19][20]24,25,30 Ureteropelvic atresia or aplastic ureters are found in people with renal cysts. 20,24 Some congenital forms of human cystic renal disease are associated with cystic changes in the pancreas and liver.…”
Section: Resultsmentioning
confidence: 99%
“…Pig congenital polycystic kidneys, which exhibited an enlarged phenotype resulting distended abdomen, contained numerous cysts throughout the cortex and medulla (Webster and Summers, 1978). Wells et al (1980) reported a 47.5% prevalence of renal cysts in an abattoir investigation. Renal cysts with variable sizes and numbers were seen in the affected pigs.…”
Section: Discussionmentioning
confidence: 98%